KT-PERFUSION DYNAMICS OF A BRAIN AT PATIENTS WITH SYMPTOMATIC EPILEPSY AT TREATMENT WITH PREGABALIN - A. S. Shershever; M. A. Zhuravlyov; S. A. Lavrova; E. V. Sorokov; E. A. Grebenev (Эпилепсия и пароксизмальные состояния, 2016)
Influence of Pregabalin on brain KT-perfusion condition at 28 patients (21 men and 7 women) at the age from 17 till 35 years (middle age 27±8,18 years) with various forms of symptomatic epilepsy during the period 2008-2011gg is studied. All patients applied various antiepileptic means. Frequency of EP from 5-17 (±11,4) in a month. Prior to the beginning of application Pregabalin to all patients KT-perfuse of a brain is made. On a brain KT series before intravenous introduction of 50 ml Omnipac 300 and at KT-perfusion research at 87 % of patients in temporal shares and in cortical departments, near Sylvie’s crack are revealed the hipoperfusion centers with decrease in indicators of CBV, CBF and strengthening peak to level of values of white substance of a brain. Asymmetries of values on other parametrical cards in the field in comparison with a counterlateral hemisphere aren’t defined. These data coincided with results of EEG. Probably at patients with epilepsy chronic ischemia of certain structures of a brain, especially against absence of effect from PEP carried out before therapy that leads to chronical ischemia of a brain is formed. In 30-60 days, after addition to used PEP Pregabalin EP reduction at 61,7 % of patients for 78 % and the termination – 38,9 % is noted. Positive dynamics in the form of improvement and perfusion normalization in temporal shares and cortical departments, near Sylvie’s crack in 77 % is revealed. These data coincided with results of EEG. At repeated KT perfusion in 12 months these results remained. Patients who independently stopped reception Pregabalin recurrence of EP and a former picture of a hipoperfusionis noted. Application of Pregabalin promoted reduction of quantity of attacks at patients with various forms of symptomatic epilepsy that led to improvement of a perfusion of a brain